Teaching Grammar At University: Integrating Linguistic, Discourse, And Pragmatic Aspects - Fethiza Tedjani, Mouna (جامعة الوادي - University of Eloued, 2022)
Abstract:The present study aims to offer a context bounded model of grammar teaching that integrates insights from discourse analysis and pragmatics without neglecting or prioritising the role of formal knowledge of rules. The suggested pedagogical framework aims to raise the awareness of students of English as a foreign language in Algeria to interpret and produce grammar rules_ articles in this respect as a teaching situation _ to ultimately develop students' abilities to cope with communicative needs. The selected grammatical items will be taught through discourse and analysed in terms of form function relationship, the cohesive role of grammatical elements under scrutiny in discourse, and the acts the utterances fulfill. A definite comprehensible teaching framework is suggested to teach grammar from an eclectic angle. Once the students are acquainted with sufficient discourse-based content, they are expected to promote their production and interpretation abilities in communicative situations efficiently and appropriately .
مقال
Keywords: Grammar1; Pragmatics2; Discourse Analysis3; Teaching4; Communicative abilities5.